From the ethology of animals to the human ecology - Łepko, Zbigniew (Studia Ecologiae et Bioethicae, 2013)
The title "From the ethology of animals to human ecology" acknowledges both the theories of evolution developed in numerous scientific fields of science and the academic achievements of Konrad Lorenz and his partners, the development of which are shown through the order of studies they published, from the scope of classical ethology and the row of humanities to philosophy and human ecology. Lorenz conducted an ethological examination of human culture, thereby uncovering its biological bases, its dynamics, social pathologies, and means for overcoming them. Thanks to this Lorenz gained an insight into the character of the crisis of contemporary civilization, described and diagnosed it, presented the causes, and proposed a cure. Lorenz recommended mobilizing efforts to create an ecological ethos for those surviving on Earth. Today it isn't possible to predict the future of Homo sapiens on our planet, however, we have a duty to prepare for our struggle to survive. It is not only about survival but to the preservation of the human way of life. This is a matter of biological and spiritual survival. Therefore, Lorenz's ethological humanism takes on the mantle of a new 'evolutionary humanism".